Biosynthetic mechanism of very long chain polyunsaturated fatty acids in Thraustochytrium sp. 26185 - Meesapyodsuk, Dauenpen (J Lipid Res, 2016)
Thraustochytrium, a unicellular marine protist, has been used as a commercial source of very long chain PUFAs (VLCPUFAs) such as DHA (22:6n-3). Our recent work indicates coexistence of a Δ4-desaturation-dependent pathway (aerobic) and a polyketide synthase-like PUFA synthase pathway (anaerobic) to synthesize the fatty acids in Thraustochytrium sp. 26185. Heterologous expression of the Thraustochytrium PUFA synthase along with a phosphopantetheinyl transferase in Escherichia coli showed the anaerobic pathway was highly active in the biosynthesis of VLCPUFAs. The amount of Δ4 desaturated VLCPUFAs produced reached about 18% of the total fatty acids in the transformant cells at day 6 in a time course of the induced expression. In Thraustochytrium, the expression level of the PUFA synthase gene was much higher than that of the Δ4 desaturase gene, and also highly correlated with the production of VLCPUFAs. On the other hand, Δ9 and Δ12 desaturations in the aerobic pathway were either ineffective or absent in the species, as evidenced by the genomic survey, heterologous expression of candidate genes, and in vivo feeding experiments. These results indicate that the anaerobic pathway is solely responsible for the biosynthesis for VLCPUFAs in Thraustochytrium.